Menua Mulia dan Penuh Makna: Pendekatan Psikologi Islam dalam Merawat Kesehatan Mental Lansia - Rahma Fitri; Aji Pangestu; Annisa Indah Nur Khusnul Fatimah (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
The increasing number of older adults in Indonesia poses significant challenges to mental health, particularly regarding depression, loneliness, and diminished sense of meaning in later life. In a predominantly religious society, integrating developmental psychology with spiritual values is essential to support the psychological well-being of older adults. This study aimed to examine the effectiveness of a mental health psychoeducation program integrating developmental psychology and Islamic values in improving participants’ understanding of meaningful aging. A quantitative pre-experimental design with a one-group pretest–posttest approach was employed involving 37 older adult participants. Data were collected using knowledge questionnaires administered before and after the intervention and were analyzed using the Wilcoxon Signed Rank Test due to non-normal data distribution. The findings revealed a statistically significant difference between pre-test and post-test scores (p < 0.05), with a mean increase of 17.03 points and a very large effect size (r=0.88). These results indicate that psychoeducation integrating clinical-developmental psychology and Islamic spirituality is effective in enhancing mental health literacy among older adults and has the potential to support ego integrity and psychological well-being. This model offers practical implications for developing holistic and culturally contextualized community-based mental health programs for older populations.